Targeted DamID detects cell-type-specific histone modifications in intact tissues or organisms - van den Ameele, Jelle; Trauner, Manuel; Hörmanseder, Eva; Donovan, Alex P. A.; Llorà-Batlle, Oriol; Cheetham, Seth W.; Krautz, Robert; Yakob, Rebecca; Malkowska, Anna; Gurdon, John B.; Brand, Andrea H. (PLoS biology, 2025)
Histone modifications play a key role in regulating gene expression and cell fate during development and disease. Current methods for cell-type-specific genome-wide profiling of histone modifications require dissociation and isolation of cells and are not compatible with all tissue types. Here we adapt Targeted DamID (TaDa) to recognize specific histone marks, by fusing chromatin-binding proteins or single-chain antibodies to Dam, an Escherichia coli DNA adenine methylase. When combined with TaDa, this enables cell-type-specific chromatin profiling in intact tissues or organisms. We first profiled H3K4me3, H3K9ac, H3K27me3 and H4K20me1 in vivo in neural stem cells of the developing Drosophila brain. Next, we mapped cell-type-specific H3K4me3, H3K9ac and H4K20me1 distributions in the developing mouse brain. Finally, we injected RNA encoding DamID constructs into 1-cell stage Xenopus embryos to profile H3K4me3 distribution during gastrulation and neurulation. These results illustrate the versatility of TaDa to profile cell-type-specific histone marks throughout the genome in diverse model systems.